2017
DOI: 10.1097/acm.0000000000001503
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time for Entrustable Professional Activities for Residency Program Directors?

Abstract: Residency program directors (PDs) play an important role in establishing and leading high-quality graduate medical education programs. However, medical educators have failed to codify the position on a national level, and PDs are often not recognized for the significant role they play. The authors of this Commentary argue that the core entrustable professional activities (EPAs) framework may be a mechanism to further this work and define the roles and responsibilities of the PD position. Based on personal obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Another potential benefit of this framework is that it can serve as a guide for recruitment and promotion of facilitators [20]. For this purpose, one proposed method is granting a 'statement of awarded responsibility' (STAR) to the teacher demonstrating sufficient proficiency in an EPA [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential benefit of this framework is that it can serve as a guide for recruitment and promotion of facilitators [20]. For this purpose, one proposed method is granting a 'statement of awarded responsibility' (STAR) to the teacher demonstrating sufficient proficiency in an EPA [2].…”
Section: Discussionmentioning
confidence: 99%
“…For the past decade, much work has been done in developing and implementing EPAs in both undergraduate [17] and postgraduate [18] medical training programs. Some studies have reported the utility of EPAs for simulation leaders [19], program directors [20], and scholars [21]. Most recently, EPAs have been introduced for training health professional educators [22,23] and family medicine teachers [24].…”
Section: Introductionmentioning
confidence: 99%
“…Overarching goals of clinical electives are clearly stated and foster a better understanding and concreteness of needed clinical skills [12], [13]. On the one side, the students know what they can expect from their ward training, and on the other side, the supervisors also know which professional activities they can entrust to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Some have proposed that it may be time for a set of entrustable professional activities (EPAs) for residency program directors. 7 As the TABLE illustrates, most of these EPAs map well to the core competency areas addressed in the typical MHPE program. Moreover, many MHPE programs can be tailored to the learner's needs and interests, and specific tracks can be crafted to further enhance the relevance of the MHPE degree to GME leadership activities.…”
Section: Degree and Certificate Programs In Health Professions Educationmentioning
confidence: 96%
“…4 In addition, with the advent of the Next Accreditation System and the Clinical Learning Environment Review program, program directors are expected to thoroughly understand how to review curriculum, grow and develop educational expertise among their own faculty, and create and maintain a robust evaluation system for milestones reporting. 7,9,10…”
Section: A Growing Educational Needmentioning
confidence: 99%